Selected breast cancer risk factors and early detection of the neoplasm in women from Lublin region attending screening program in St. John’s Cancer Center, years 2005–2006 - Jolanta Anna Surdyka; Dariusz Surdyka; Andrzej Stanisławek; Elżbieta Starosławska; Krzysztof Ireneusz Patyra (Annals of Agricultural and Environmental Medicine, 2014)
[b]introduction and objective[/b]. In Poland, consulting is offered to women about risk factors of breast cancer, breast symptoms and early cancer detection. Study aims were to evaluate the correlation between some risk factors and women’s attendance to breast checkups, and to assess links between risk factors and detection of early breast cancer. [b]materials and methods. [/b]The study involved 8014 women aged 50–69 years, participating in breast cancer screening program. The frequency of breast checkups (mammography, CBE and BSE) and occurrence of breast cancer risk factors in studied women were evaluated as well as clinical stage of detected tumors. Odds ratios were used to compare relative odds of breast cancer with exposure to risk factors. [b]results. [/b]47.11% studied women had regularly undergone MMG, 30.82% had CBE within the previous year, 14.26% regularly performed BSE. The incidence of risk factors varied from 2.94% (menarche at ≤ 11 years) to 12.38% (current use of HRT). In 47.82% women, no evidence of studied risk factors was found. Women with history of breast biopsies and current users of HRT had MMG, CBE and BSE significantly more often ( p<0.0001). 29.27% early breast cancers (pTis, pT1abN0) were found among 82 detected tumors. Relative odds of breast cancer occurrence in women without the risk factors were significantly lower (OR = 0.55, 95% CI [0.35; 0.86]). Only nulliparous women had significantly higher odds of early breast cancer (OR = 7.37, 95% CI [1.32; 41.17]). [b]conclusions. [/b]Women using HRT and women after breast biopsy were significantly more likely to attend breast checkups. There were no significant links between most risk factors and odds of early stages of breast cancer. Women should have preventive checkups irrespective of their breast cancer risk factors.